Is there (still) an emerging progressive majority in the United States? - Teixeira, Ruy (Sens public, 2010)
A political scientist renown for his works on the Democrats, Ruy Teixeira is a Senior Fellow at both The Century Foundation and The Center for American Progress. In this text written at the request of Sens Public, he explains what he sees for the future of both the progressive movement and America.